DRY EYE SYNDROME: PATHOPHYSIOLOGY, DIAGNOSIS AND PREVENTIVE STRATEGIES (International journal of medical sciences, 2026)
Dry Eye Syndrome (DES), also known as keratoconjunctivitis sicca (KCS), is a multifactorial disorder of the tear film and ocular surface, characterized by tear film instability, hyperosmolarity, ocular discomfort, and visual disturbances. DES affects millions worldwide, significantly reducing quality of life and productivity. This review synthesizes current scientific understanding of DES pathophysiology, risk factors, diagnostic criteria, and evidence-based preventive strategies.